Hatchery seed production of flat oysters from the Mar Menor lagoon - Hernandis, Sebastián; da Costa, Fiz; Hernández-Contreras, Ángel; Albentosa, Marina (Frontiers in Marine Science, 2023)
The Mar Menor lagoon (SE Spain) suffers a severe eutrophication process aggravated since the collapse of the lagoon in 2016. Together with it, the populations of the flat oyster Ostrea edulis have been decimated in the lagoon, but also in the European seas, where the species and the habitats provided by it have mainly disappeared. The Mar Menor Oyster Initiative’s main objectives are gaining knowledge on the nutrient extraction capability of the Mar Menor flat oyster and developing the required tools for restoration and bioextraction actions. The project RemediOS, within the framework of the Mar Menor Oyster Initiative, aims to obtain flat oyster seed using the decimated local broodstock to provide the initiative with an oyster population to work with. The present work describes the results of the first attempt of Mar Menor local broodstock reproduction in captivity. Larvae produced in the hatchery accounted for 57.5 million, of which 11.8 million were cultured and 0.68 million survived to settlement and metamorphosis.